Fixed-wing Unmanned Aerial Vehicle (UAV) Prototype as a Tool for Delivering Aid Packages in Disaster-affected Areas - Hasin, M. Khoirul; Rinanto, Noorman; Ulya, A. Arif Zuchal; Subiyanto, Lilik; Rahmat, M. Basuki; Mudjiono, Urip (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
Delays in delivering aid, especially medicines, to areas affected by natural disasters can prolong the suffering of victims and increase the risk of death. Therefore, in this study we propose the creation of a fixed-wing (FW) UAV prototype that is capable of carrying emergency aid in the form of medicines to remote or isolated areas after a natural disaster. This type of UAV is capable of flying long distances with sufficient payload to deliver emergency aid to remote areas that are difficult to reach. This prototype is made with a balsa wood frame and a Styrofoam aircraft body. In addition, the prototype is equipped with a number of sensors such as GPS, altitude, speed, and digital cameras. To monitor the condition, position, and communication of the UAV while carrying out a mission, the operator on the ground is equipped with Ground Control System (GCS) software. The results of testing both mechanically, electrically, and software showed good performance so that this prototype is ready to be operated in areas affected by natural disasters.